KONSTRUKSI MAKNA RITUAL RUWATAN TANI DALAM KOMUNIKASI BUDAYA MASYARAKAT PENGHAYAT DESA CIKOLE - Dice Surya Putra; Ira Aryanti Rasyi Lubis (Yayasan Literasi Sains Indonesia, 2026)
The Tani Ruwatan Ritual is a form of local wisdom still maintained by indigenous believers in Kampung Cibedug, Cikole Village, Lembang District, West Bandung Regency. This ritual not only functions as an expression of gratitude for agricultural yields, but also serves as a medium of cultural communication representing the harmonious relationship among humans, nature, and God. This study aims to analyze how the meaning of the Tani Ruwatan ritual is constructed through communication interaction between indigenous believers and non-believers. The study employs a qualitative approach with a phenomenological method. Data were obtained through in-depth interviews, observation, and documentation, and then analyzed using Peter L. Berger and Thomas Luckmann's social construction model, which includes the processes of externalization, objectivation, and internalization. The results show that the meaning of the ritual is built through cultural symbols, collective experience, and intergenerational communication that continues to be passed down. On the other hand, the indigenous believers adapt their communication through collaboration with the Muslim community and the utilization of digital media to broaden public understanding without eliminating the sacred values of the ritual. This study contributes to the development of cultural communication studies, particularly regarding the process of constructing local cultural meanings in a multicultural society amidst social change influenced by modernization and information technology development.